DPR Debate : Should Industrial Policy in Developing Countries Conform to Comparative Advantage or Defy It? A Debate between Justin Lin and Ha-Joon Chang - Lin, Justin; Chang, Ha-Joon (2012)
This is the first in an occasional series of DPR Debates, designed to illuminate specific issues of international development policy. Each debate will bring together two well-known researchers or practitioners, giving them the opportunity, over three rounds, to test and challenge each other's ideas. The debates are intended to be robust but accessible, rooted in rigorous research but useful to the wide readership of Development Policy Review.